Recent advances in strategies for inhibiting Leidenfrost effect - Huaduo GU; Mingyu LI; Jiahao ZHANG; Zuankai WANG (Journal of Thermal Science and Technology, 2025)
The rapid progression of industrialization and the integration of artificial intelligence in recent years emphasizes the critical need for efficient thermal cooling solutions. Despite significant strides in technology, existing liquid cooling methods, notably boiling heat transfer and spray cooling, encounter substantial obstacles attributable to the well-documented Leidenfrost effect. Upon contact with a highly heated surface, a liquid generates a vapor layer that acts as an insulator, elevating the liquid above the surface and severely impeding heat transfer efficiency. While notable advancements have been achieved in mitigating the Leidenfrost effect, a comprehensive understanding of the underlying mechanisms remains limited. Furthermore, challenges persist in sustaining high-temperature environments across diverse structures, materials, and technologies, impeding progress in this domain. This review aims to provide a thorough account of fundamental tactics for suppressing the Leidenfrost phenomenon on high-temperature substrates. It will underscore distinctive attributes and challenges while exploring avenues for the development of efficient and sustainable thermal management solutions.